PARTISIPASI MASYARAKAT DALAM PENYELENGGARAAN SEKOLAH DASAR DI PERIGI KECAMATAN SUELA LOTIM NTB - Aswasulasikin Aswasulasikin (Educatio, 2009)
This study aimed to investigate the: (1) forms of community participation in administering elementary school at Perigi, (2) strategies to increase the community participation in administering elementary school at Perigi, and (3) obstacles of community participation in administering elementary school at Perigi. This study is an empirical study using a descriptive qualitative approach. The subject of research was determined using the purposive sampling method. Data collected through observation, interview, documentation, and were analyzed using the Interactive Model techniques from Miles and Huberman. Subject In this study, school principals, heads of school committees, young people, and community. The result of analysis shows that: (1) the people at Perigi only participated when they were asked to share work in building school facilities, but they are not involved in planning, conducting, and evaluating. (2) school principals, together with the heads of school committees, come to the community only when some students are absent from school, but no efforts or strategies conducted by the school and local government to increase the community participation in other ways, (3) The obstacles for community participation in running elementary education at Perigi are the low level of educational background of the community, the low level of people’s income, and the culture.Keywords: community participation, primary school, Lombok Timur